Quadruple treatment with doxycycline, furazolidone, bismuth and proton pump inhibitor is still effective against Helicobacter pylori in our population - Barreda-Costa, Carlos S. (2023)
Our objective is to determine the effectiveness of a therapeutic regimen for helicobacter pylori that includes a proton pump inhibitor, doxycycline, furazolidone and bismuth in our location. We carried out a retrospective study, non-randomized, in a private hospital in Lima, Peru. Patients with biopsy and/or rapid urease test proven helicobacter pylori infection after an endoscopy, from January 2017 to October 2022 were included. They received the therapeutic regimen of the study or an alternative triple regimen with a proton pump inhibitor, amoxicillin and levofloxacin and were followed with a urea breath test within 1 to 6 months upon completion of therapy. The quadruple therapy with furazolidone obtained success in 117/122 cases (95.9%) while the triple therapy with levofloxacin only in 5/16 (31.2%) when used for 7 days and 22/38 (57.9%) when used for 10 days, a statistically significant difference with p<0.001. Conclusion: Quadruple therapy with furazolidone reached high effectiveness in our location, while triple therapy with levofloxacin was not an acceptable alternative.